2010
DOI: 10.1016/j.jsbmb.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-term DHEA treatment on glucose metabolism, hydrogen peroxide and thioredoxin levels in the skeletal muscle of diabetic rats

Abstract: Dehydroepiandrosterone (DHEA) is an endogenous steroid hormone involved in a number of biological actions. This study shows the effects of DHEA on glucose metabolism, hydrogen peroxide and thioredoxin levels in the skeletal muscle of control and diabetic rats. Control and diabetic rats were chronically treated with DHEA (10mg/kg) diluted in oil. Plasma concentration of DHEA and glucose, glucose uptake and oxidation, hydrogen peroxide, GLUT4, Akt and thioredoxin (Trx) was measured in the muscle. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Sato et al ( 44 ) reported that GLUT-4 protein expression level was increased and the glucose metabolic signaling pathway was activated in skeletal muscle cells following DHEA-treatment. Jahn et al ( 45 ) demonstrated that muscle glucose oxidation was increased by 120% in diabetic Wistar rats treated with DHEA. Thus, the effect of DHEA on succinate dehydrogenase activity may be associated with its energy-wasting properties.…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al ( 44 ) reported that GLUT-4 protein expression level was increased and the glucose metabolic signaling pathway was activated in skeletal muscle cells following DHEA-treatment. Jahn et al ( 45 ) demonstrated that muscle glucose oxidation was increased by 120% in diabetic Wistar rats treated with DHEA. Thus, the effect of DHEA on succinate dehydrogenase activity may be associated with its energy-wasting properties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, youngest rats present high levels of testosterone (400 pg/ml), declining significantly with aging, dropping more than 90% when the animal achieves 22 months of age [46]. Both DHEA and testosterone are known to increase the basal metabolism as demonstrated by the augmented cellular respiratory activity in young rats hepatocytes [47] and by the increase in glucose uptake in skeletal muscle in young rats [32]. Studies have also described that steroid hormones present a tissue-dependent effect in the rat muscle thus leading to a more pro-oxidant environment [48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also described that steroid hormones present a tissue-dependent effect in the rat muscle thus leading to a more pro-oxidant environment [48, 49]. Finally, treatment with DHEA caused a 2-fold decrease in thioredoxin antioxidant enzyme expression in skeletal muscle of young rats [32]. Taking all these evidence together, it is possible that the higher levels of H 2 O 2 observed in 3-months-old rats could be a consequence of a set of factors, including an augmented basal metabolism and a not-fully adapted antioxidant defense system favoring a pro-oxidant environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dehydroepiandrosterone (DHEA) is produced by the adrenal cortex and synthesized from pregnenolone and is further metabolized to androstenedione, testosterone, and estrogens (Aoki & Terauchi, 2018). Additionally, it can be synthesized in the central and peripheral nervous system (Jahn et al, 2010). Moreover, DHEA is regarded as a neurosteroid due to its impact on the brain's neurotransmitter receptors.…”
mentioning
confidence: 99%